2021
DOI: 10.1038/s41598-021-97837-9
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of gap and step-off measurements in acetabular fracture treatment

Abstract: The assessment of gaps and steps in acetabular fractures is challenging. Data from various imaging techniques to enable accurate quantification of acetabular fracture displacement are limited. The aim of this study was to assess the accuracy of pelvic radiographs, intraoperative fluoroscopy, and computed tomography (CT) in detecting gaps and step-offs in acetabular fractures. Sixty patients, surgically treated for acetabular fractures, were included. Five observers (5400 measurements) measured the gaps and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, postoperative CT scans showed 11 cases with a step shift greater than 2 mm and 24 cases with gap shift greater than 1 cm. Meesters et al [22] measured the step and space displacement in postoperative X-ray and CT scans of patients with acetabular fractures and re-evaluated the intraoperative imaging results, and found that compared with postoperative CT, the X-ray images missed 52% of the gap and 80% of the step displacement, and intraoperative X-ray images missed approximately 70% of the residual gap and step displacement. Although previous studies have shown that CT has certain advantages in evaluating the quality of acetabular fracture reduction, due to the poor mobility of conventional CT equipment and the increased radiation dose to doctors and patients, no scholars currently use conventional CT to evaluate fracture reduction during surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postoperative CT scans showed 11 cases with a step shift greater than 2 mm and 24 cases with gap shift greater than 1 cm. Meesters et al [22] measured the step and space displacement in postoperative X-ray and CT scans of patients with acetabular fractures and re-evaluated the intraoperative imaging results, and found that compared with postoperative CT, the X-ray images missed 52% of the gap and 80% of the step displacement, and intraoperative X-ray images missed approximately 70% of the residual gap and step displacement. Although previous studies have shown that CT has certain advantages in evaluating the quality of acetabular fracture reduction, due to the poor mobility of conventional CT equipment and the increased radiation dose to doctors and patients, no scholars currently use conventional CT to evaluate fracture reduction during surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that CT scans can provide more accurate and detailed information than radiographs in evaluating the quality of acetabular fracture reduction [4,13,21,22]. Moed et al [13] performed postoperative CT scans on 67 cases of acetabular posterior wall fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are concerns regarding the interobserver reliability of radiographic measurements even though these measurements are still the gold standard in clinical practice 5,20 . Gap and step-off measurements in particular are prone to interobserver variability 21,22 , although measurements of tibial alignment have shown good reliability 23,24 . Nevertheless, intraobserver measurements within this study showed good reliability for all measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Meesters et al 1 analyzed incongruity in acetabular fractures and concluded that 52% of gaps and 80% of step-offs visible using computed tomography were missed on radiographs. In addition, radiographs underestimated the size of the detected gaps or step-offs by a factor of 2.…”
Section: Commentarymentioning
confidence: 99%